Earthquakes Recent Advances, New Perspectives and Applications - Salazar, Walter (IntechOpen, 2023)
Earthquakes - Recent Advances, New Perspectives and Applications is a compilation of nine chapters covering aspects of tectonics, seismicity, earthquake forecasting, geotechnical engineering, and buildings. It presents state-of-the-art techniques for calculating moment tensors, rupture inversions, and hypocentral locations. It also presents methodologies to test probabilistic earthquake distributions on clustered and declustered catalogs and improves on classical methodologies to estimate bearing capacity and slope stability analysis. The final section discusses the structural behavior of vernacular and modern structures in the nonlinear range and the consequences of modifying the original structural system of a building.